О приближенных решениях нечетких дифференциальных уравнений в пространстве E2 - Слинько, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
A new approach to the construction of approximate solutions of the fuzzy differential equations in the E2 space is proposed. A support function approximation of fuzzy sets by Fejer sums is supposed to the base of the approach.